Disruption of Mitochondria-Associated Endoplasmic Reticulum Membrane (MAM) Integrity Contributes to Muscle Insulin Resistance in Mice and Humans - Tubbs, Emily; Chanon, Stéphanie; Robert, Maud; Bendridi, Nadia; Bidaux, Gabriel; Chauvin, Marie-Agnès; Ji-Cao, Jingwei; Durand, Christine; Gauvrit-Ramette, Daphné; Vidal, Hubert; Lefai, Etienne; Rieusset, Jennifer (Diabetes (New York, N.Y.), 2018)
Modifications of the interactions between endoplasmic reticulum (ER) and mitochondria, defined as mitochondria-associated membranes (MAMs), were recently shown to be involved in the control of hepatic insulin action and glucose homeostasis, but with conflicting results. Whereas skeletal muscle is the primary site of insulin-mediated glucose uptake and the main target for alterations in insulin-resistant states, the relevance of MAM integrity in muscle insulin resistance is unknown. Deciphering the importance of MAMs on muscle insulin signaling could help to clarify this controversy. Here, we show in skeletal muscle of different mice models of obesity and type 2 diabetes (T2D) a marked disruption of ER-mitochondria interactions as an early event preceding mitochondrial dysfunction and insulin resistance. Furthermore, in human myotubes, palmitate-induced insulin resistance is associated with a reduction of structural and functional ER-mitochondria interactions. Importantly, experimental increase of ER-mitochondria contacts in human myotubes prevents palmitate-induced alterations of insulin signaling and action, whereas disruption of MAM integrity alters the action of the hormone. Lastly, we found an association between altered insulin signaling and ER-mitochondria interactions in human myotubes from obese subjects with or without T2D compared with healthy lean subjects. Collectively, our data reveal a new role of MAM integrity in insulin action of skeletal muscle and highlight MAM disruption as an essential subcellular alteration associated with muscle insulin resistance in mice and humans. Therefore, reduced ER-mitochondria coupling could be a common alteration of several insulin-sensitive tissues playing a key role in altered glucose homeostasis in the context of obesity and T2D.